2022
DOI: 10.1186/s12934-022-01766-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors influencing expression and extraction of recombinant bacteriophage endolysins in Escherichia coli

Abstract: Background Endolysins are peptidoglycan hydrolases with promising use as environment-friendly antibacterials mainly when used topically. However, in general, endolysin expression is hampered by its low solubility. Thus, a critical point in endolysin industrial production is optimizing their expression, including improvement of solubility and recovery from cell extracts. Results We report the expression of two endolysins encoded in the genome of pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…In this context, N-L is an anionic surfactant with multiple applications in biotechnology and biomedicine, including transdermal drug delivery [27][28][29], fabrication of biomaterials and nanomaterials [30][31][32], structural protein analysis [33,34], separation of co-purified tag-less proteins from protein complexes [35]and mild protein solubilization/extraction [36][37][38], among many others. In fact, it was the first non-denaturing agent used in the solubilization of recombinant proteins from IBs [39].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, N-L is an anionic surfactant with multiple applications in biotechnology and biomedicine, including transdermal drug delivery [27][28][29], fabrication of biomaterials and nanomaterials [30][31][32], structural protein analysis [33,34], separation of co-purified tag-less proteins from protein complexes [35]and mild protein solubilization/extraction [36][37][38], among many others. In fact, it was the first non-denaturing agent used in the solubilization of recombinant proteins from IBs [39].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been conducted to improve the existing E. coli-based protein expression. Balaban et al demonstrated the use of osmolytes, such as N-lauroylsarcosine, to increase the expression rate of E. coli C43 (DE3) from the existing 30-40% to about 54% (Balaban et al, 2022). Engineered strains of E. coli BL21 (DE3), viz., BL21Star (DE3) that offers enhanced mRNA stability, BL21trxB (DE3) that promotes correct folding of proteins and formation of disulphide bonds, and BL21 (DE3) pLysS that lowers the leaky expression of the gene of interest, are examples of E.coli expression systems that have been developed and found superior to their counterparts (Jia and Jeon, 2016).…”
Section: Expression Systems For the Production Of Recombinant Lysinsmentioning
confidence: 99%
“…Studies have been conducted to improve the existing E. coli- based protein expression. Balaban et al demonstrated the use of osmolytes, such as N-lauroylsarcosine, to increase the expression rate of E. coli C43 (DE3) from the existing 30–40% to about 54% ( Balaban et al, 2022 ). Engineered strains of E. coli BL21 (DE3), viz.…”
Section: Expression Systems For the Production Of Recombinant Lysinsmentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics, in particular, make them promising alternatives to antibiotics [9,10]. In this context, the expression of endolysin from different phages via microbial cells as a chassis has attracted the attention of an increasing number of researchers [11][12][13][14]. A number of Salmonella-specific endolysins have been identified and characterized recently (Additional file 1: Table S1).…”
Section: Introductionmentioning
confidence: 99%